In vivo assessment of optimal b-value range for perfusion-insensitive apparent diffusion coefficient imaging - Freiman, Moti; Voss, Stephan D.; Mulkern, Robert V.; Perez-Rossello, Jeannette M.; Callahan, Michael J.; Warfield, Simon K. (Medical physics (Lancaster), 2012)
Purpose: To assess the optimalb-values range for perfusion-insensitive apparent diffusion coefficient (ADC) imaging of abdominal organs using short-duration DW-MRI acquisitions with currently available ADC estimation methods. Methods: DW-MRI data of 15 subjects were acquired with eightb-values in the range of 5–800 s/mm2. The reference-standard, a perfusion insensitive, ADC value (ADCIVIM), was computed using an intravoxel incoherent motion (IVIM) model with all acquired diffusion-weighted images. Simulated DW-MRI data was generated using an IVIM model with b-values in the range of 0–1200 s/mm2. Monoexponential ADC estimates were calculated using: (1) Two-point estimator (ADC2); (2) least squares three-point (ADC3) estimator and; (3) Rician noise model estimator (ADCR). The authors found the optimal b-values for perfusion-insensitive ADC calculations by minimizing the relative root mean square error (RRMS) between the ADCIVIM and the monoexponential ADC values for each estimation method and organ. Results: Lowb-value = 300 s/mm2 and high b-value = 1200 s/mm2 minimized the RRMS between the estimated ADC and the reference-standard ADCIVIM to less than 5% using the ADC3 estimator. By considering only the in vivo DW-MRI data, the combination of low b-value = 270 s/mm2 and high b-value of 800 s/mm2 minimized the RRMS between the estimated ADC and the reference-standard ADCIVIM to <7% using the ADC3 estimator. For all estimators, the RRMS between the estimated ADC and the reference standard ADC correlated strongly with the perfusion-fraction parameter of the IVIM model (r = [0.78–0.83], p ≤ 0.003). Conclusions: The perfusion compartment in DW-MRI signal decay correlates strongly with the RRMS in ADC estimates from short-duration DW-MRI. The impact of the perfusion compartment on ADC estimations depends, however, on the choice ofb-values and estimation method utilized. Likewise, perfusion-related errors can be reduced to <7% by carefully selecting the b-values used for ADC calculations and method of estimation.